Exploring students' digital informal learning: the roles of digital competence and DTPB factors. Issue 13 (3rd October 2021) - He, Tao; Huang, Qionghao; Yu, Xiaofeng; Li, Shihua
ABSTRACT : Learning approaches enhanced by digital technologies have gained considerable attention in higher education. Prior research has mainly focused on digital technology adoption in formal learning settings of higher education. Yet, empirical research into discerning what influences a student's digital informal learning has not been well investigated. This paper proposes that individuals' digital competence affects their digital informal learning (DIL) intention and actual behaviour. To understand better learners' DIL and the effects of digital competence, we integrated digital competence into the decomposed theory of planned behaviour (DTPB) model and tested the model by using survey data from university students in Belgium. Here, we have explored different aspects of their DIL behaviours of cognitive, meta-cognitive, social and motivational learning. The findings showed both attitudinal factors in DTPB and digital competence adequately explained students' DIL. Finally, the roles of digital competence and other DPTB factors are discussed in students' DIL.